ε-Poly-l-lysine Suppressed Decay Development and Maintained Storage Quality in Guava Fruit by ROS Level Regulation and Antioxidant Ability Enhancement - Yingying An; Li Li; Mingming Wen; Feng Luo; Mei Tan; Yuzhao Lin; Hongbin Chen (Agriculture)
Guava fruit is susceptible to decay, leading to losses in storability and quality. ε-Poly-l-lysine (ε-PL) is a safe antimicrobial polypeptide that has proven to be effective in preserving produce’s quality. In the present research, ε-PL, at multiple concentrations (1, 2 and 4 g/L), was adopted to treat guavas, and the fruit were stored at 25 °C for 15 d. The results indicated that ε-PL retarded the guava storability decline and enhanced its quality. Treated guavas had a better appearance, as well as the lower disease index, relative electrolytic leakage, weight loss, respiration intensity, a* and b* values and reducing sugar content. They also showed higher firmness, commercially acceptable fruit rate, titratable acidity, L* value, total soluble sugar, vitamin C and sucrose levels. The optimal concentration of ε-PL was determined to be 2 g/L. Furthermore, compared to control guavas, fruit treated with 2 g/L ε-PL exhibited lower levels of superoxide anion, hydrogen peroxide and malondialdehyde but higher antioxidant enzyme activities in terms of ascorbate peroxidase, peroxidase, catalase and superoxide dismutase. These findings suggested that ε-PL raised the antioxidant enzyme activities to enhance the fruit’s antioxidant ability. This, in turn, reduced the reactive oxygen species levels and lipid peroxidation, ultimately improving the guava’s quality. Consequently, ε-PL is of practical significance for commercial application as it suppresses decay and stabilizes the quality of guavas, enhancing their postharvest marketability.